Policies lost in translation? : Unravelling water reform processes in African waterscapes - Kemerink-Seyoum, Jeltsje Sanne, author (Leiden, the Netherlands : CRC Press/Balkema, 2015)
Thesis (Doctorate)--Delft University of Technology, 2015